â€œPengaruh Fraud Risk Assessment dan Kecakapan Auditor Terhadap Kualitas Audit Dalam Pengawasan Keuangan Daerahâ€ (Studi pada Kantor Inspektorat Provinsi Sulawesi Tenggara) - Solichin, Dinan Azmi (JURNAL AKUNTANSI, 2016)
This study aims to determine the effect of fraud risk assessment and auditor skills to audit authorities in the financial on the provinces (Study in the Regional Inspectorate of Sulawesi Tenggara Provinces). The study is a survey with census method, while spreading technique using questionnaires distributed to regional fungsional Inspectorate Sulawesi Tenggara Province were 23 respondents. Respondents perception measured by the answer of questionnairs used ordinal measurement with 5 likert scale. The statistical methods used to multiple regression analysis. The analysis showed that the significant F value 0f F 0,002 < α=0,05. In other words the fraud risk assessment and auditor skills simultaneously significantly audit quality decisions at the level of 95%. T significance value (fraud risk assessment) of 0,049 < α=0,05, indicating that the fraud risk assessment is partially significant effects on audit quality. Significant value t (auditor skills) of 0,048 < α=0,05, also indicates that the quality of the auditor skills significant effect on audit quality. Coefficient Adjust R Squre of Regressions is 46,9% while the remaining 53,1% are influence by other factor (ɛ). This case shows that the fraud risk assessment and auditor skills shall be used and to have by all APIP especially in Inspectorate Sulawesi Tenggara Province to produce a better quality. Keywords: Fraud Risk Assessment, Auditor Skills and Audit Quality